2021
DOI: 10.1371/journal.pone.0259663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional variants of vitamin C transporter genes on apolipoprotein E E4-associated risk of cognitive decline: The Nakajima study

Abstract: Apolipoprotein E E4 (APOE4) is a risk factor for cognitive decline. A high blood vitamin C (VC) level reduces APOE4-associated risk of developing cognitive decline in women. In the present study, we aimed to examine the effects of functional variants of VC transporter genes expressed in the brain (SLC2A1, SLC2A3, and SLC23A2) on APOE4-associated risk of developing cognitive decline. This case–control study involved 393 Japanese subjects: 252 cognitively normal and 141 cognitively impaired individuals (87 mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Previous research has found a strong link between VC deficiency and cognitive disorders. By functional single nucleotide variants (SNVs) of VC transporter genes, altered VC levels in the brain increase the risk of developing cognitive decline associated with Apolipoprotein E E4 (APOE4) [ 47 ], and plasma VC levels correlate with markers of the metabolic health and cognitive impairment to a large extent [ 48 ]. VC deficiency is common in older hospitalized patients and is associated with cognitive impairment, according to a cross-sectional study [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found a strong link between VC deficiency and cognitive disorders. By functional single nucleotide variants (SNVs) of VC transporter genes, altered VC levels in the brain increase the risk of developing cognitive decline associated with Apolipoprotein E E4 (APOE4) [ 47 ], and plasma VC levels correlate with markers of the metabolic health and cognitive impairment to a large extent [ 48 ]. VC deficiency is common in older hospitalized patients and is associated with cognitive impairment, according to a cross-sectional study [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors note that the correlation between GLUT levels and dehydroascorbic acid levels in the brain have not yet been established, given how GLUTs are nonspecific transporters and have other substrates, mainly sugars. Finally, the authors called for the investigation of the relationship between cognitive decline, dehydroascorbic acid, and GLUT expression in animal models [ 91 ].…”
Section: Recent Examples Of Glut Associated Diseasesmentioning
confidence: 99%